2009
DOI: 10.1007/978-3-642-03132-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Trust-Building in Electronic Markets: Relative Importance and Interaction Effects of Trust-Building Mechanisms

Abstract: We examine the relative and complementary effectiveness of trust-building strategies in online environments. While prior research has examined various antecedents to trust, we investigated two trust-building mechanisms more in depth: Web site trust and vendor reputation. We tried to understand the relative effectiveness of these two important mechanisms to provide online businesses with a clear recommendation of how to establish trust in an effective and efficient manner. Drawing from the literature on trust, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Jarvenpaa and Tractinsky (1999) proposed that PWR would positively affect consumers' trust in an internet shop. Tams (2009) found that web vendors' reputations had a significant influence on consumers' trust in them as well.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Jarvenpaa and Tractinsky (1999) proposed that PWR would positively affect consumers' trust in an internet shop. Tams (2009) found that web vendors' reputations had a significant influence on consumers' trust in them as well.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Doney and Cannon (1997) also indicated that when a buying firm trusts the selling firm, it will trust the salesperson of the selling firm more. Tams (2009) demonstrated that website trust had a positive effect on vendor trust. Similarly people may be more willing to trust that the recommendations of most members of a website are useful when they also trust the quality and management of the website.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%